Being-With-Algorithm: Psychotherapists’ Lived Experiences of Artificial Intelligence and the Therapeutic Relationship - Monadi, Mojdeh; Mohammadi, Rezgar; Kiani, Ahmadreza (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: The present study aimed to explore psychotherapists’ lived experiences of artificial intelligence and its perceived influence on the therapeutic relationship within contemporary psychotherapy practice. Methods and Materials: This study employed a qualitative phenomenological design using Interpretative Phenomenological Analysis (IPA). The participants consisted of 20 psychotherapists practicing in Tehran, Iran, selected through purposive sampling with maximum variation based on therapeutic orientation, years of experience, and familiarity with artificial intelligence technologies. Inclusion criteria included a minimum of three years of clinical experience and prior exposure to AI-assisted therapeutic or professional tools. Data were collected through semi-structured in-depth interviews lasting between 60 and 95 minutes. Interview questions focused on therapists’ experiences regarding empathy, therapeutic presence, ethical concerns, professional identity, emotional authenticity, and human-AI interaction in psychotherapy. Interviews were audio-recorded, transcribed verbatim, and analyzed using iterative phenomenological coding procedures. Strategies including member checking, peer review, reflexive memo writing, and audit trail documentation were employed to enhance trustworthiness and credibility. Findings: The findings revealed that psychotherapists experienced artificial intelligence through a complex coexistence of acceptance, ambivalence, and existential concern. Five superordinate themes emerged from the data: AI as a clinical companion, threats to therapeutic presence, ethical and professional ambivalence, reconfiguration of therapist identity, and human-AI coexistence in therapy. Participants acknowledged the usefulness of AI for administrative efficiency, cognitive support, and clinical organization while simultaneously expressing concerns regarding emotional dehumanization, diminished empathic attunement, weakened authenticity, and ethical uncertainty. Therapists emphasized that empathy, emotional resonance, and relational presence were fundamentally human dimensions that could not be authentically replicated by algorithmic systems. The emergence of AI also prompted deeper reflection on the uniqueness of human therapeutic engagement and the preservation of relational centrality within psychotherapy. Conclusion: The findings suggest that psychotherapists perceive artificial intelligence as both a valuable professional resource and a potential challenge to the relational foundations of psychotherapy. Although AI technologies may enhance efficiency and accessibility, therapists continue to regard authentic human connection, emotional attunement, and existential understanding as irreplaceable components of therapeutic healing. The future integration of AI into psychotherapy therefore requires careful ethical regulation, professional adaptation, and preservation of human-centered therapeutic values.